Fabrication and property of discarded denim fabric/polypropylene composites. (March 2015) - Wei, Baochun; Xu, Fujun; Azhar, Sayed Waqar; Li, Wei; Lou, Luyang; Liu, Wei; Qiu, Yiping
In this study, discarded denim fabric was adopted to enhance the mechanical and thermal properties of polypropylene (PP). The composites with different fiber weight fractions were designed and fabricated by using a hand layup and hot pressing method. The tensile, impact, and flame-retardant properties of the composites were investigated and their morphology was observed by scanning electron microscopy. Owing to the integrity structure and good mechanical property of denim fabric, the tensile strength and impact strength of the 84 wt% denim-reinforced composite were up to 57 MPa and 5.1 J/mm, which super exceed those of the ramie/PP composites (26 MPa) and flax/PP composites (0.36 J/mm). In addition, the flame-retardant properties of the composites were modified by three methods. The results showed that the composites composed of flame-retardant-modified denim fabric exhibited the limiting oxygen index value of 27.3%, much higher than that of the modified PP composites (<19.2%) and untreated composites (<19.2%). Composites made by using flame-retardant PP and modified denim fabric simultaneously attained highest limiting oxygen index at 28.7%. The discarded denim fabric/PP composites showed good mechanical and flame-retardant properties and thus could substitute the traditional composites in automotive interior, packing materials and engineering materials.